2001
DOI: 10.1007/s100530170066
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced fragmentation and neutralization of methanol cluster cations

Abstract: This contribution addresses the inelastic interaction of positively charged molecular cluster ions with a solid surface at kinetic energies up to 30 eV/molecule. We report experimental results on the scattering of mass-selected, protonated methanol cluster cations (CH3OH)nH + , n = 4−32, off a diamondcoated silicon surface. In particular we provide fragment size distributions of methanol cluster ions following their impact on the target, as well as surface-induced neutralization probabilities of methanol clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Moreover, in a similar manner high energy impact of cluster ions on surfaces has also been described in terms of complete shattering of the clusters 18,19 ͓see also ͑i͒ other pioneering studies in this field including Refs. 20-30 and ͑ii͒ some of the recent studies [31][32][33][34][35][36][37][38][39] ͔. It is interesting to note here that all of these distribution patterns obtained in cluster ion fragmentation studies are similar to what has been observed earlier in nuclear fragmentation reactions.…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, in a similar manner high energy impact of cluster ions on surfaces has also been described in terms of complete shattering of the clusters 18,19 ͓see also ͑i͒ other pioneering studies in this field including Refs. 20-30 and ͑ii͒ some of the recent studies [31][32][33][34][35][36][37][38][39] ͔. It is interesting to note here that all of these distribution patterns obtained in cluster ion fragmentation studies are similar to what has been observed earlier in nuclear fragmentation reactions.…”
Section: Introductionsupporting
confidence: 82%
“…[6][7][8][9] At the same time clusterimpact experiments have been carried out by several groups. 13 For lower impact velocities the clusters can be generated by supersonic expansion. The velocity of impact is controlled by a second electric field that is retarding the approach to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The largest peak in Figure is that of the lone p -difluorobenzene (P) ion. The spectrum is also dominated by a series of protonated methanol (M) peaks, (M n =3−14 H + ) that form via proton transfer reactions in neat ionized methanol clusters . A small occurrence of the P 2 + dimer is also noted.…”
Section: Resultsmentioning
confidence: 95%